Decomposing the U.S. Great Depression: How important were Loan Supply Shocks? - Max Breitenlechner; Johann Scharler (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
We evaluate contributions of exogenous loan supply shocks to output dynamics during the Great Depression. Based on a structural VAR, we impose sign restrictions to identify loan supply shocks in addition to standard macroeconomic shocks. Our results indicate that the banking panics that occurred in the early 1930s were associated with negative loan supply shocks, supporting the view that disruptions in financial intermediation contributed significantly to the severity of the Great Depression.
Keywords: C32; E32; E44; N12; N22; 330